Data processing and reconciliation for chemical process operations - Romagnoli, José A; Sánchez, Mabel Cristina (Process systems engineering, 2000)
Computer techniques have made online measurements available at every sampling period in a chemical process.However, measurement errors are introduced that require suitable techniques for data reconciliation and improvements in accuracy.